Literasi Media Digital dan Pencegahan Hoaks bagi Masyarakat Desa Molantadu - Wahidah Suryani; Taufik R Talalu; Hidayatullah Hidayatullah; Dwi Jaya Arisyana; Taufik Ajuba; Wardoyo Dingkol; Sumarlin Adam; Ahmad Faruq Ananda Mashudhin; Candrawan Kaida (Yayasan Inspirasi El Burhani, 2026)
Introduction: The rapid growth of digital media in Indonesia has made access to information easier but has also increased the public’s vulnerability to hoaxes and misinformation, particularly in rural areas. This condition is evident in Molantadu Village, Tomilito District, North Gorontalo Regency, where many residents have fallen victim to online scams and false information. Objective: The purpose of this community service was to enhance the digital media literacy of Molantadu villagers, especially their ability to recognize, verify, and prevent the spread of hoaxes through social media platforms. Method: This public service activity was carried out by lecturers from the Islamic Communication and Broadcasting Study Program, Faculty of Ushuluddin and Da’wah, IAIN Sultan Amai Gorontalo, in collaboration with the Government of Molantadu Village. The program consisted of three main stages: preparation, implementation, and evaluation. It was conducted in three interactive training sessions over two days, involving 30 participants. Evaluation was conducted through observation, pre-test and post-test questionnaires, and reflective group discussions. Result: The results indicate a significant improvement in participants’ understanding of digital literacy, with an average increase of 47.7% across all measured aspects. Participants demonstrated enhanced skills in identifying hoaxes, verifying factual information, and refraining from sharing unverified content. Conclusion: This community service program successfully improved the digital literacy skills of Molantadu villagers. The findings suggest that a participatory training model emphasizing practical exercises and small-group discussions is effective in fostering critical awareness among rural communities toward digital information. This program is recommended for replication in other villages to strengthen community resilience against hoaxes and misinformation.